Trends, Methods, and Perspectives of Education Curriculum in Indonesia Towards the Quality and Outcomes of Physics Learning Using the Bibliometric Approach - Hanan Zaki Alhusni; Akhmad Iswardani; Titin Sunarti; Hanandita Veda Saphira; Muhammed Akif Kurtuluş (Journal of Law and Bibliometrics Studies, 2025)
Objective: This study aims to map related keywords and identify research trends concerning the Indonesian physics curriculum, with a focus on quality and learning outcomes, in order to uncover potential directions for future research. It also seeks to provide an overview of research topics that have been most frequently explored, especially those indexed in the Scopus database. Method: This study employed a bibliometric analysis approach using data retrieved from the Scopus database. The analysis focused on publications related to the Indonesian curriculum in physics education from 1977 to 2024. The parameters analyzed included keyword co-occurrence, most productive authors, and frequently targeted journals. Results: The bibliometric analysis identified 287 articles related to the Indonesian curriculum. The most frequently occurring keywords were curriculum, quality education, curriculum development, and curriculum evaluation. The most prolific author in this field was Didi S. Meanwhile, the Journal of Physics: Conference Series appeared as the journal with the most publications related to curriculum and science literacy. These results indicate a continuing interest in curriculum-related research within the scope of physics education in Indonesia. Novelty: This study offers a systematic mapping of Indonesian curriculum research trends in physics education over nearly five decades. It highlights underexplored areas and presents evidence-based insights into future research opportunities, particularly in integrating curriculum studies with physics learning outcomes. The findings contribute to strategic planning for researchers and policymakers aiming to enhance curriculum development in Indonesia.